The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/life12091358
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection and Response to Vaccination in Chronic Kidney Disease and Renal Transplantation: A Brief Presentation

Abstract: Chronic kidney disease (CKD) is associated with phenotypic and functional changes in the immune system, followed by detrimental clinical consequences, such as severe infections and defective response to vaccination. Two years of the pandemic, due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), have undoubtedly changed the world; however, all efforts to confront infection and provide new generation vaccines tremendously improved our understanding of the mechanisms of the immune response against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…As MGRS is associated in its pathophysiology with dysfunctions of B cell maturation and proliferation, there are indications that vaccines targeting these processes, such as mRNA vaccines, may be implicated in exacerbations of the disease [ 1 , 2 , 3 ]. Furthermore, this patient’s clinical course after vaccination is congruent with this hypothesis, based on the mechanistic understanding proposed by other research results from our clinical center [ 4 ].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…As MGRS is associated in its pathophysiology with dysfunctions of B cell maturation and proliferation, there are indications that vaccines targeting these processes, such as mRNA vaccines, may be implicated in exacerbations of the disease [ 1 , 2 , 3 ]. Furthermore, this patient’s clinical course after vaccination is congruent with this hypothesis, based on the mechanistic understanding proposed by other research results from our clinical center [ 4 ].…”
Section: Introductionsupporting
confidence: 84%
“…Recent studies have shown that levels of CD4+CD38+HLADR+ and CD8+CD38+HLADR+ activated T cells are substantially increased three weeks after vaccination [ 30 ]. Our results also showed that antibodies against the receptor binding domain of SARS-Cov-2 S protein, as well as neutralizing antibodies, were raised in CKD patients after mRNA vaccination for COVID-19, with the main increase at the first and second month after the second dose [ 4 ]. This timeframe corresponds to the time our patient had a relapse.…”
Section: Discussionmentioning
confidence: 94%
“…Risk factors predisposing to adverse outcomes comprise old age; male gender; and several comorbidities, including kidney disease and immunodeficiencies [6]. Being significantly immunocompromised mainly due to the use of immunosuppressants and presenting with a pleiad of coexisting medical conditions, kidney transplant recipients (KTRs) have a higher incidence of COVID-19 infection and are more prone to the development of severe disease complications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the first two years of the pandemic, a considerable number of different vaccines against SARS-CoV-2 were developed, including messenger RNA (mRNA), inactivated virus, viral vector and recombinant protein-based platforms [8,9]. Tozinameran (BNT162b2), a nucleoside-modified mRNA vaccine created by Pfizer-BioNTech, has been the most widely used one among Greek KTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that levels of CD4 + CD38 + HLADR+, CD8 + CD38 + HLADR + activated T cells are substantially increased three weeks after vaccination (4). Our own results also showed that antibodies against the Receptor Binding Domain (RBD) of SARS-Cov-2 S protein as well as Neutralizing Antibodies (NAB) were raised in CKD patients after mRNA vaccination for Covid-19, with the main increase at 1st and 2nd month after the second dose (5). This timeframe corresponds to the time the patient had relapse.…”
Section: Discussionmentioning
confidence: 66%